Implementasi Strategi Komunikasi Organisasi terhadap Semangat Kerja Pegawai PT. Cendana Wahana Gemilang - Rafi Rahmat Djajasumitra; Yuliani Rachma Putri; Almira Shabrina (Universitas Batanghari, 2022)
PT. Cendana Wahana Gemilang or often known as CWG (Car Wash Gue) is a company engaged in the automotive and culinary fields, ranging from car and motorcycle washes, car and motorcycle repair shops, sales of vehicle accessories as well as food and beverage culinary fields. With the COVID-19 pandemic, of course, the company's various goals are hampered and indirectly also affects the morale of the employees. It is possible to find a decrease in employee morale that is felt by the management. This research was conducted with the aim of knowing how the organizational communication strategy of PT. Cendana Wahana Gemilang which affects the morale of the employees, as well as knowing what factors support and also hinder the implementation of the organization's communication strategy. The research method used is qualitative using an interpretive descriptive approach, and data collection is done by means of interviews, observations, and structured documentation. The results of this study indicate that PT. Cendana Wahana Gemilang implements organizational communication strategies to maintain employee morale by communicating the stages of organizational communication strategies based on predetermined phases, PT. Cendana Wahana Gemilang composes a message based on the Human Resources organizational approach and provides motives for the need for achievement, the need for power and the need for affiliation to its employees to maintain morale, as well as evaluating to knowing the supporting factors and also the inhibiting factors of the organizational communication strategy that has been carried out by the company.